The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.17221/3738-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing germination of kiwifruit seeds with temperature, medium and gibberellic acid

Abstract: Germination responses to temperature, medium and gibberellic acid (GA3) treatments were studied in kiwifruit (Actinidia deliciosa Chev. cv. Hayward) seeds. The seeds treated with four GA3 concentrations (0, 2,000, 4,000 and 6,000 ppm) were sown in trays with peat moss, perlite + heater humus and soil mixture and subjected to the temperatures of 20°C, 25°C, 30°C and 35°C with bottom heating, under controlled conditions. All the treatments significantly affected the kiwifruit seeds germination. Seeds sown in pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…New, mature kiwifruit seeds did not germinate when placed in favourable conditions for germination at any of the tested temperatures. This result is consistent with the findings for the same species presented in previous reports (Lawes and Anderson, 1980; Chin et al ., 1992; Celik et al ., 2006). The failure of germination can be attributed to primary seed dormancy established during seed maturation on the mother plant (Hilhorst, 1995; Kucera et al ., 2005; Finch-Savage and Leubner-Metzger, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…New, mature kiwifruit seeds did not germinate when placed in favourable conditions for germination at any of the tested temperatures. This result is consistent with the findings for the same species presented in previous reports (Lawes and Anderson, 1980; Chin et al ., 1992; Celik et al ., 2006). The failure of germination can be attributed to primary seed dormancy established during seed maturation on the mother plant (Hilhorst, 1995; Kucera et al ., 2005; Finch-Savage and Leubner-Metzger, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Stratification under cool and moist condition or gibberellic acid treatment improves germination rates. Treatment with 2500ppm of gibberellic acid gives 31.67% germination [55]. The higher concentration of gibberellic acid of about 2000ppm to 6000ppm for 24 hours shortens the germination period.…”
Section: Introductionmentioning
confidence: 97%
“…Although some studies showed that gibberellic acid can enhance kiwifruit seed germination [4,11,12], other studies indicated that cold moist stratification is more effective than gibberellic acid in breaking kiwifruit seed dormancy [8,9,13]. They also found that vermiculite is not a suitable medium for seed germination.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, for sustainable production and export, the kiwifruit industry needs to introduce novel kiwifruit cultivars with different flesh colors and flavors. To achieve this goal, a population of seed plants with natural or controlled crosses should be available [4]. The presence of dormant embryos in seeds and nonuniformity in seedling growth usually increase the losses of kiwifruit seed populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation